Identifying and assessing sustainable value management implementation activities in developing countries: The case of Egypt - Kineber, A.F. (MDPI, 2020)
Value management (VM) has become a useful tool for achieving sustainability in many countries. This paper aims to assess VM implementation and its activities towards achieving sustainable building projects in Egypt. Data were obtained from the literature, followed by a qualitative approach through a semi-structured interview and a quantitative approach via a questionnaire survey. In Cairo and Giza, data were collected from a sample of 200 building professionals using a questionnaire, while exploration of the countryâs VM activities practice was completed using exploratory factor analysis (EFA), including descriptive statistics such as âfrequency analysisâ and âmeasures of central tendenciesâ. The results show that VM awareness was demonstrated by 64 of the sample, which means that they know about VM. On the other hand, most respondents, 85.3, did not adopt VM and did not receive any VM training. The results also show, through EFA, that the correlations between these activities show five main components: an information phase, a function phase, a creativity phase, an evaluation phase, and a development/presentation phase. This study will help building professionals to eliminate unwanted costs and enhance project sustainability by adopting VM in building projects in developing countries. Finally, the results of this study will enhance building management through the implementation of VM elements, with a view to ensuring value for money and meeting sustainability goals. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.